On the Nature of Fear and Anxiety Triggered by COVID-19 - Coelho, Carlos M.; Suttiwan, Panrapee; Arato, Nikolett; Zsido, Andras N. (Frontiers in Psychology, 2020)
Emergencies that occur during natural disasters such as avalanches, earthquakes, and floods tend to be sudden, unexpected, and ephemeral and recruit defensive responses, similar to the ones recruited when faced with dangerous animals (Zsido, et al., 2020). Defensive behaviors are triggered by activity in survival circuits that detects imminent threats and fear is the conscious emotion of that follows immediately. But this particular threat (COVID-19) is useable and mysterious, triggering anxieties much more than fear. We conducted a literature search on 1 May 2020 in Google Scholar, PsychInfo, and Pubmed with search terms related to COVID-19 fears and found 28 relevant articles. We categorized the papers into six groups based on the content and implications: fear of the unknown, social isolation, hypochondriasis, disgust, information-driven fears, and compliance. Considering the nature of fear and anxiety, combined with the characteristics of the present COVID-19 situation, we contemplate that physicians and other health care workers of several specialties, as well as police officers, fire-fighters, and rescue personnel, and first responders might be more able to deal with COVID-19 if they have a) some tolerance of the unknown, b) low illness anxiety disorder, c) tolerance to social isolation; d) low levels of disgust sensitivity; e) be granted financial support, f) have priority if needed medical assistance g) use caution relatively to the COVID-19 media coverage and h) be trained to have high levels of efficacy. Possibilities for preventive and therapeutic interventions that can help both health care personnel and the general population are also discussed.